2007
DOI: 10.1101/gr.6675307
|View full text |Cite
|
Sign up to set email alerts
|

Islands of euchromatin-like sequence and expressed polymorphic sequences within the short arm of human chromosome 21

Abstract: The goals of the human genome project did not include sequencing of the heterochromatic regions. We describe here an initial sequence of 1.1 Mb of the short arm of human chromosome 21 (HSA21p), estimated to be 10% of 21p. This region contains extensive euchromatic-like sequence and includes on average one transcript every 100 kb. These transcripts show multiple inter- and intrachromosomal copies, and extensive copy number and sequence variability. The sequencing of the “heterochromatic” regions of the human ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
(34 reference statements)
5
26
1
Order By: Relevance
“…Much of the presently-available HC21p sequence contains SDs (Lyle et al 2007), and we found that many of the HC21p AS sequences are also duplicated elsewhere in the genome. A short region of AF105153 is duplicated on chromosome 16, while small portions of CU638690 are also found on either chromosome 7 or 16.…”
Section: Characterization Of Hc21 Bacs/cosmidsmentioning
confidence: 60%
See 1 more Smart Citation
“…Much of the presently-available HC21p sequence contains SDs (Lyle et al 2007), and we found that many of the HC21p AS sequences are also duplicated elsewhere in the genome. A short region of AF105153 is duplicated on chromosome 16, while small portions of CU638690 are also found on either chromosome 7 or 16.…”
Section: Characterization Of Hc21 Bacs/cosmidsmentioning
confidence: 60%
“…This cell line contains, as its only human material, 1-5 copies per cell of HC21 which lacks major deletions or rearrangements (Lyle et al 2007). Illumina pair-end sequencing libraries were constructed from 1 μg of WAV-17 DNA using the TruSeq DNA Sample Prep v2 Kit according to the manufacturer's protocol.…”
Section: Deep Sequencing Reads and Wav-17 Testmentioning
confidence: 99%
“…Heterochromatic regions are reported to contain many transcriptionally active genes (Lyle et al 2007). Some constitutively heterochromatic regions become transcriptionally active in response to stress stimuli such as heat shock (Rizzi et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Although centromeric regions are commonly associated with compact, gene-poor heterochromatin, segmental duplications have been credited with "euchromatic colonization," introducing transcriptionally active landscapes capable of genetic innovation in the vicinity of centromeres (She et al 2004). In the human genome, characterized non-satellite euchromatic-like islands exist within the satellite-rich regions on chromosome 21p and in the pericentromeric region of chromosome Yq11 and, similarly, may represent a new dataset of previously uncharacterized segmental duplications within the inter-array "transitions" missing from our genomic model (Kirsch et al 2005;Lyle et al 2007). One may also speculate that even novel, single-copy sequences could occupy these regions through centromeric repositioning, establishing centromere identity within a region of the genome that, over time, is enclosed by satellite expansion (Montefalcone et al 1999).…”
Section: A Genomic Model Of Human Centromeresmentioning
confidence: 99%